2021
DOI: 10.1016/j.contraception.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Changes to medication abortion clinical practices in response to the COVID-19 pandemic

Abstract: Objectives: To document medication abortion clinical practice changes adopted by providers in response to the COVID-19 pandemic. Study design: Longitudinal descriptive study, comprised of three online surveys conducted between April to December, 2020. We recruited sites from email lists of national abortion and family planning organizations. Results: Seventy-four sites opted to participate. We analyzed 55/74 sites (74%) that provided medication abortion and completed all three surveys. The total number of abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 19 publications
0
53
0
2
Order By: Relevance
“…Telehealth was not available, but if offered there would have likely been an increase in medication abortions. There was a 27% increase in the rate of requests for medication abortion at home within the first month of the pandemic across the United States, with larger increases in states with more abortion restrictions 11 . In the United Kingdom, research during the pandemic found no difference between telemedicine abortion and traditional in-person care in terms of effectiveness or adverse events 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth was not available, but if offered there would have likely been an increase in medication abortions. There was a 27% increase in the rate of requests for medication abortion at home within the first month of the pandemic across the United States, with larger increases in states with more abortion restrictions 11 . In the United Kingdom, research during the pandemic found no difference between telemedicine abortion and traditional in-person care in terms of effectiveness or adverse events 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has documented substantial constraints in accessing contraceptive and abortion care early in the pandemic, 4 , 5 , 29 , 30 , 31 , 32 followed by implementation of novel approaches to expand access to care via telehealth, mail order, and pharmacies. 33 , 34 Given that social and economic disruptive events can cause population-level increases in people’s desire to prevent or postpone pregnancy, continued implementation and evaluation of these expanded care models will be important to attain reproductive autonomy during future disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). We then ranked states into quartiles, categorizing each state as having low (0-4 points), medium (5)(6)(7)(8)(9)(10)(11)(12), high (13)(14)(15)(16)(17), or extreme (18-20) abortion restrictions (Supplemental Table 1). To separately estimate the association of global abortion hostility from the effect of laws that specifically prohibit care innovations such as no-exam visits and telemedicine, we created a separate binary variable to indicate if state-level restrictions specifically mandated a visit for medication abortion care by requiring either (1) an ultrasound or (2) in-person dispensing of mifepristone as a state law, in addition to the FDA requirement.…”
Section: Methodsmentioning
confidence: 99%